Analisis Penerapan Keterampilan Memberi Penguatan Guru Pendidikan Agama Kristen dalam Meningkatkan Motivasi Belajar Siswa Kelas XI SMA Negeri 1 Siborongborong Tahun Ajaran 2019/2020 - Siregar, Esrani (Areopagus : Jurnal Pendidikan Dan Teologi Kristen, 2020)
The research aims is to knowthe application of skills to strengthen PAK teachers in improving student motivation in class XI of SMAN 1 Siborongborong in the Academic Year 2019/2020. The research hypothesis is the application of skills to strengthen PAK teachers in increasing student motivation in class XI of SMAN 1 Siborongborong in 2019/2020 75% of 100% expected. The population is all students of class XI of SMA Negeri 1 Siborongborong in the 2019/2020 Academic Year who are Protestant Christians, amounting to 397 people. The research sample was determined by random sampling (random) by 15% of 397 people, namely 62 people. This research method is quantitative inferential method. The instrument used in this study was a questionnaire. Hypothesis testing using the t test formula obtained t-count = 28.422 t-table = 2,000. T value is in the region of rejection curve H0 and Ha reception. Thus, it can be concluded that the research hypothesis is accepted, namely the application of skills to strengthen PAK teachers in increasing student learning motivation in class XI of SMAN 1 Siborongborong, Academic Year 2019/2020 75% of 100% expected. Achieving the application of skills to strengthen PAK teachers in increasing student motivation in class XI of SMAN 1 Siborongborong in the Academic Year 2019/2020 is 3.46 in the good category with a large percentage of 86.55% in the very strong category.Â Keywords :Application of Skills Gives Strengthening of PAK Teachers, Improving StudentLearning Motivation.